Low-cost nano biochar: a sustainable approach for drought stress mitigation in faba bean (Vicia faba L.) - Abd El-Moaty, Heba Ibrahim; El-Dissouky, Ali; Elhusseiny, Amel F.; Farag, Kareem M.; Abu-Khudir, Rasha; Alkuwayti, Mayyadah Abdullah; Al Abdulsalam, Najla K.; Abdel Rahman, Salwa M. (Frontiers in Plant Science, 2024)
This study tends to reach some objectives of the sustainable development goals, which call for responsible consumption and production and climate action. Long-term global food security is affected by drought and the optimal use of water in agricultural areas under climate change scenarios. Our approach aims to amend soil for cultivation under drought stress and improve plant growth to contribute to food security. In this context, a biochar was prepared from peanut shell and thoroughly examined as a soil enhancer for broad bean cultivation during drought stress. The produced biochar exhibited 0.307 g cm−3 bulk density, 9.6 cmol kg−1 cation exchange capacity, −15.5 mV zeta potential, and an average diameter of 21.86 nm. Surprisingly, the application of biochar increased soil water holding capacity and organic matter by 66% and 220%, respectively. Moreover, its application under drought improved plant growth as indicated by stem height, leaf area index, pod number/plant, pod weight, protein level, chlorophyll content, nutrient levels in leaves, and reduced lipid peroxidation and electrolyte leakage. The principal component and factorial analysis of the current study demonstrated correlations between the physiological response of faba bean plants and soil physiochemical parameters after the application of peanut shell-derived biochar. This study presents promising nano biochar that could be an effective sustainable practice for disposing residual materials.